Memorjał w sprawie Urzędników Niemców w Bibliotece Miejskiej - przyczynek do polonizacji instytucji bydgoskich u progu dwudziestolecia międzywojennego (Kronika Bydgoska, 2018)
The beginning of the twenty-year interwar period marked re-Polonization and Polonization of offices, production plants and cultural centers, including the Municipal Library. It was founded in 1903 and was a German institution serving the purposes of Germanization. The mission of its adjustment to the new political and social conditions was assigned to Dr. Witold Bełza, who replaced its personnel, Polonized and expanded its book collection. Memorandum Concerning the German Employees in the Municipal Library, written on March 4, 1921 and sent to the Municipal Office of Bydgoszcz, refers to this process. Its main topic is the dispute between the Polish director, W. Bełza and its German deputy, P. Biedermann. The letter perfectly describes the process of de-Germanization of this Bydgoszcz institution shown as an example, since it concerns many problems, particularly relations between employees representing both nations and between Germans themselves, and their different approach to the changing political conditions.